Odpowiedź :
Odpowiedź:
[tex]a)\\\\x(x-5)=2x(x-1)\\\\x^2-5x=2x^2-2x\\\\x^2-5x-2x^2+2x=0\\\\-x^2-3x=0\\\\-x(x+3)=0\ \ /\cdot(-1)\\\\x(x+3)=0\\\\x=0\ \ \ \ \vee\ \ \ \ x+3=0\\\\x=0\ \ \ \ \vee\ \ \ \ x=-3[/tex]
[tex]b)\\\\\frac{x+3}{x-3}=\frac{6}{x-3}\ \ \ \ \ \ x\neq 3\ \ \ \ D=R\setminus\left\{3}\right\}\\\\x+3=6\\\\x=6-3\\\\x=3\\\\Liczba\ \ 3\ \ nie\ \ spelnia\ \ zalo\.zenia\ \ wiec\ \ r\'ownanie\ \ nie\ \ ma\ \ rozwiazania[/tex]
[tex]c)\\\\5x(x+3)(4x-2)=0\\\\5x=0\ \ /:5\ \ \ \ \vee\ \ \ \ x+3=0\ \ \ \ \vee\ \ \ \ 4x-2=0\\\\x=0\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=-3\ \ \ \ \ \ \ \ \vee\ \ \ \ 4x=2\ \ /:4\\\\x=0\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ x=-3\ \ \ \ \ \ \ \ \vee\ \ \ \ x=\frac{1}{2}[/tex]